Obligasi Syariah Sebagai Instrumen Investasi dalam Sistem Keuangan di Indonesia - Ismail Puhi (Al-Ulum, 2010)
This article describes the development of Islamic financial institutions in Indonesia recently. It raises the need for a variety of banking financial system. By the increasing in Islamic financial institutions, the market share of Islamic economy will eventually grow. The growth adds a large capitalization of accumulated capital. Large funds will seek investment placement forms that vary in line with the desired portfolio. One solution to the needs of the accumulated fund is the issuance of bonds, because the investments instruments that have the big market share are obligation. Therefore, issuers and investors as the market participants should be able to know definition and differences of each bond issuance